Improved Hybrid Current Regulation for Interior PMSM Drives Subjected to Internal/External Distortions - Mohammed, Sadeq Ali Qasem; Lee, Kyo Beum (2023 IEEE International Symposium on Sensorless Control for Electrical Drives, SLED 2023, 2023)
This paper designs a hybrid control strategy for interior permanent magnet synchronous motors (IPMSM) in the presence of internal/external disturbances. It combines two control approaches, i.e., adaptive control that is activated during the steady-state condition and iterative learning control (ILC) which is activated only at the transient condition. Therefore, the proposed hybrid control merges the robustness of the adaptive control against system uncertainty while the ILC improves the tracking performance hence achieving improved dynamic and steady-state control performance regardless the changing disturbances. Contrary to the conventional method, the proposed method maintains a satisfactory control operation (e.g., fast dynamic response, small steady-state error, etc.) by stabilizing the state errors to approach zero and compensating for the model parameter variations. To prove the effectiveness of the proposed control approach, it is simulated on a PSIM simulation tool and implemented on a prototype of PMSM drive powered by 2 level (2L)-inverter.
Keywords: Adaptive Control; Control approach; Current regulations; External distortion; Hybrid current control; Hybrid currents; Interior permanent magnet synchronous motor; Internal distortion; Iterative learning control; PMSM drives; External distortion; hybrid current control; interior permanent magnet synchronous motors; internal distortion